Death of a Simulated Pediatric Patient: Toward a More Robust Theoretical Framework. Issue 6 (December 2017) - McBride, Mary E.; Schinasi, Dana Aronson; Moga, Michael Alice; Tripathy, Shreepada; Calhoun, Aaron
Abstract : Introduction: A theoretical framework was recently proposed that encapsulates learner responses to simulated death due to action or inaction in the pediatric context. This framework, however, was developed at an institution that allows simulated death and thus does not address the experience of those centers at which this technique is not used. To address this, we performed a parallel qualitative study with the intent of augmenting the initial framework. Methods: We conducted focus groups, using a constructivist grounded theory approach, using physicians and nurses who have experienced a simulated cardiac arrest. The participants were recruited via e-mail. Transcripts were analyzed by coders blinded to the original framework to generate a list of provisional themes that were iteratively refined. These themes were then compared with the themes from the original article and used to derive a consensus model that incorporated the most relevant features of each. Results: Focus group data yielded 7 themes. Six were similar to those developed in the original framework. One important exception was noted; however, those learners not exposed to patient death due to action or inaction often felt that the mannequin's survival was artificial. This additional theme was incorporated into a revised framework. Discussion: The original framework addresses most aspects of learner reactions to simulated death. Our work suggests that adding the theme pertaining to the lack of realism that can be perceived when the mannequin is unexpectedly saved results in a more robust theoretical framework transferable to centers that do not allow mannequin death.